2023
DOI: 10.1021/acs.jmedchem.3c00249
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Based Discovery of a New Selectivity-Enabling Motif for the FK506-Binding Protein 51

Abstract: In recent years, the selective inhibition of FKBP51 has emerged as a possible treatment for chronic pain, obesityinduced diabetes, or depression. All currently known advanced FKBP51-selective inhibitors, including the widely used SAFit2, contain a cyclohexyl residue as a key motif for enabling selectivity over the closest homologue and anti-target FKBP52. During a structure-based SAR exploration, we surprisingly discovered thiophenes as highly efficient cyclohexyl replacement moieties that retain the strong se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 51 publications
0
1
0
Order By: Relevance
“…We tested the effects of two FKBP5 inhibitors, SAFit1 and SAFit2, on the adipogenesis of FAPs and found that both drugs effectively inhibited adipogenic differentiation, reducing the expression of adipogenic promoting factors. Currently, SAFit1 and SAFit2 is at a nascent stage, with most studies focusing on their cellular and molecular effects, and have not yet progressed to clinical trials [ 36 ]. Translating these findings into practical treatments requires careful balancing act.…”
Section: Discussionmentioning
confidence: 99%
“…We tested the effects of two FKBP5 inhibitors, SAFit1 and SAFit2, on the adipogenesis of FAPs and found that both drugs effectively inhibited adipogenic differentiation, reducing the expression of adipogenic promoting factors. Currently, SAFit1 and SAFit2 is at a nascent stage, with most studies focusing on their cellular and molecular effects, and have not yet progressed to clinical trials [ 36 ]. Translating these findings into practical treatments requires careful balancing act.…”
Section: Discussionmentioning
confidence: 99%
“…FKBP51 has emerged as a promising drug target for chronic pain, obesity, , and depression. , The major challenge in FKBP51 drug development is selectivity toward its closest homologue FKBP52, as the binding pockets of both proteins are very similar, but the biological functions are opposite. Selectivity for FKBP51 can be achieved by targeting a transient conformation characterized by an outward flip of phenylalanine 67 (F67 in and F67 out , Figure A). This conformation is rarely populated in the apo-state of FKBP51, but enables high selectivity vs FKBP52. , To stabilize the transient binding pocket of FKBP51 (F67-out), we aimed to lock this conformation precisely by the formation of an intramolecular amide bond (sites displayed in Figure B). We have also explored bis-electrophiles to incorporate intramolecular cross-links between two cysteines at position 67 and 60/58.…”
Section: Introductionmentioning
confidence: 99%